2008
DOI: 10.1002/bmc.996
|View full text |Cite
|
Sign up to set email alerts
|

Liquid chromatography–electrospray tandem mass spectrometric assay suitable for quantitation of YM155, a novel small‐molecule survivin suppressant, in dog plasma

Abstract: This paper describes a sensitive and selective liquid chromatography with tandem mass spectrometry (LC-MS/MS) method for determination of the novel survivin suppressant YM155, 1-(2-methoxyethyl)-2-methyl-4,9-dioxo-3-(pyrazin-2-ylmethyl)-4,9-dihydro-1H-naphtho[2,3-d]imidazolium, which is developed for the treatment of solid tumors. This method uses a liquid-liquid extraction from 0.25 mL of dog plasma. LC separation was carried out on a Genesis Silica column (50 mm x 3.0 mm i.d.) at a flow-rate of 0.5 mL/min. C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
8
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 16 publications
1
8
0
Order By: Relevance
“…In another study, we reported that YM155 was distributed into tumors at concentrations approximately 20-fold higher than those in plasma during subcutaneous YM155 infusion to nude mice bearing human prostate cancer PC-3 (Nakahara et al, 2007). We also suggested that a transportermediated mechanism other than OCT1, OCT2 (SLC22A2), and OCT3 (SLC22A3) could be responsible for this high distribution (Minematsu et al, 2008). This hypothesis was based on the comparison of the IC 50 values of various substrates/inhibitors of OCTs on hepatocytes, cancer cell lines, and OCT-expressing cells.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…In another study, we reported that YM155 was distributed into tumors at concentrations approximately 20-fold higher than those in plasma during subcutaneous YM155 infusion to nude mice bearing human prostate cancer PC-3 (Nakahara et al, 2007). We also suggested that a transportermediated mechanism other than OCT1, OCT2 (SLC22A2), and OCT3 (SLC22A3) could be responsible for this high distribution (Minematsu et al, 2008). This hypothesis was based on the comparison of the IC 50 values of various substrates/inhibitors of OCTs on hepatocytes, cancer cell lines, and OCT-expressing cells.…”
mentioning
confidence: 86%
“…In nonclinical studies, barely any YM155 was metabolized during incubation with human cryopreserved hepatocytes (Sohda et al, 2007). Moreover, YM155 was eliminated with a high total clearance (Minematsu et al, 2008) and was mainly excreted into the bile and urine in the unchanged form and partly metabolized in rats and dogs (T. Minematsu, M. Iwai, K. Y. Sohda, T. Usui, and H. Kamimura, unpublished data). Thus, the first step of nonrenal elimination of YM155 (i.e., 71.6 -81.7% of the dose) in humans is probably uptake into the hepatocytes from the blood, followed by biliary excretion as unchanged drug (and partly by metabolism, if any).…”
mentioning
confidence: 99%
“…The YM155 concentration in each sample was determined by using liquid chromatography-tandem mass spectrometry (LC-MS/MS), as reported previously [22]. The concentration of CA, a marker of liposomal lipid [23], in each sample was measured as follows: Briefly, plasma or a tissue homogenate was added to an appropriate amount of methanol/ chloroform (1:1, v/v) followed by sonication and vigorous shaking.…”
Section: Pharmacokinetic and Biodistribution Studiesmentioning
confidence: 99%
“…In nonclinical studies, YM155 was hardly metabolized when incubated with human cryopreserved hepatocytes (Sohda et al, 2007). In a study conducted in animals, YM155 was eliminated with a high total clearance in dogs (Minematsu et al, 2008) and excreted mainly into the bile and urine as the unchanged form, and partly metabolized in rats and dogs (T. Minematsu, M. Iwai, K. Y. Sohda, T. Usui, and H. Kamimura, unpublished data). Given these previous findings, the first step in the nonrenal elimination of YM155 (i.e., 71.4 -81.7% of the dose) from the human body is likely to be through uptake into hepatocytes from the blood, followed mainly by biliary excretion as the unchanged form and possibly a small amount by metabolism.…”
mentioning
confidence: 99%
“…In nonclinical studies, YM155 was hardly metabolized when incubated with human cryopreserved hepatocytes (Sohda et al, 2007). In a study conducted in animals, YM155 was eliminated with a high total clearance in dogs (Minematsu et al, 2008) and excreted mainly into the bile and urine as the unchanged form, and partly metabolized in rats and dogs (T. Minematsu, M. Iwai, K. Y. Sohda, T. Usui, and H. Kamimura, unpublished data).…”
mentioning
confidence: 99%